Advances in Biomimetic Scaffolds for Hard Tissue Surgery - Ryszard Uklejewski; Mariusz Winiecki (Biomimetics, 2024)
Hard tissues are living mineralized tissues that possess a high degree of hardness and are found in organs such as bones and teeth (enamel, dentin, and cementum) [...]